Socialization at the University. A Qualitative Investigation on the Role of Contextual Dynamics in the Socialization of Academics - Yaşar Kondakçı; Çiğdem Haser (Turkish Educational Administration Research & Development Association, 2025)
This study investigates the role of content, context and process variables in the socialization of new faculty  members. The study was designed as a phenomenological study and utilized interview as the data collection technique. A total number of 40 new faculty members working in 12 different public universities in Turkey participated in the study. The results of the study suggest that culture, power dynamics, reward and remuneration systems, social interaction, role models, organizational trust and trust in top management as contextual factors; knowledge sharing, networking and participation as process factors playing role in the socialization of the new faculty members. When the institutions provide the conditions for context and process factors, the new faculty members express positive statements about their adaptation to the new work setting while negative statements are evident in the opposite case. It is argued that the context and process dynamics are critical in reaching affective outcomes, which are basic to ensure productive behaviors (e.g., positive attitudes toward work, high level of motivation, and job involvement) and eliminating unproductive behaviors(e.g., turnover intentions).